Effects of viral infection on passion fruit (Passiflora edulis) quality and productivity in the Republic of Korea - Choi, Minkyung (Frontiers in Plant Science, 2025)
Passion fruit (Passiflora edulis) is a widely cultivated plant in the Republic of Korea, but its cultivation is impacted by a variety of viral diseases. This study analyzed viral diseases in P. edulis and their effects on fruit quality and productivity. Surveys were conducted in a major P. edulis-producing region in the Republic of Korea from 2019 to 2022, and viral infection experiments were performed in a greenhouse test plot. The main viruses detected were East Asian passiflora virus (EAPV), papaya leaf curl Guandong virus (PaLCuGdV), cucumber mosaic virus (CMV), and Euphorbia leaf curl virus (EuLCV). Viral infection incidence increased as cultivation years increased, with EAPV showing the highest rate at five years. EAPV had the highest infection rate during the fruit enlargement stage, while CMV peaked in the early growth and flowering stages. Fruit from virus-infected P. edulis exhibited lower quality, with reduced Brix, titratable acidity, and fruit number. EAPV caused the most severe effects. The study highlights that uninfected P. edulis maintained stable productivity, demonstrating the potential for extending cultivation beyond the typical five-year period with effective disease management strategies. This underscores the importance of robust viral disease management to sustain long-term productivity in the P. edulis industry. This study provides foundational data to enhance the stability of P. edulis cultivation and prevent the spread of viral diseases, which could improve the sustainability of the industry and bolster economic resilience for farms.